2014
DOI: 10.7243/2052-6180-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Desulfomicrobium sp. strains, their sulfate- and lactate usage, production of sulfide and acetate by the strains isolated from the human large intestine

Abstract: The aim and background of the study were to investigate bacterial growth of the Desulfomicrobium sp. strains from human large intestine, and to study the processes usage of sulfate-and lactate, production of sulfide and acetate by the obtained bacteria as well as to carry out cluster and correlation analysis of these processes. Microbiology methods of the study for bacterial strains cultivation and photometric methods for determination of bacterial biomass and hydrogen sulfide concentration were used, sulfate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Such scenario implies a richer diversity in the Desulfovibrio population, albeit with a lesser collective abundance compared to Desulfobulbus . Conversely, genera such as Desulfomicrobium ( Kushkevych, 2014 ) and Desulfobacter ( Fang et al, 2019 ) were identified to a lesser extent, indicating their sparse representation in the consortium. This distribution underscores a competitive advantage for the Desulfovibrio and Desulfobulbus genera, facilitating their survival and nutrient competition in the sewage sludge origin, thereby delineating their significant ecological dominance in environments favorable to SRB.…”
Section: Resultsmentioning
confidence: 99%
“…Such scenario implies a richer diversity in the Desulfovibrio population, albeit with a lesser collective abundance compared to Desulfobulbus . Conversely, genera such as Desulfomicrobium ( Kushkevych, 2014 ) and Desulfobacter ( Fang et al, 2019 ) were identified to a lesser extent, indicating their sparse representation in the consortium. This distribution underscores a competitive advantage for the Desulfovibrio and Desulfobulbus genera, facilitating their survival and nutrient competition in the sewage sludge origin, thereby delineating their significant ecological dominance in environments favorable to SRB.…”
Section: Resultsmentioning
confidence: 99%
“…clone MFC-2-L19, Desulfobulbus propionicus strain ). The sulfate-reducing bacteria (SRB) are a heterogeneous group of microorganisms which use sulfate as an electron acceptor in the process of dissimilatory sulfate reduction [35,36]. The final product of this process is hydrogen sulfide [6,20,22,37].…”
Section: Amplification Of Gene Fragments and Illumina Sequencingmentioning
confidence: 99%
“…Intestinal sulfate-reducing bacteria and the bowel diseases. Sulfate-reducing bacteria Desulfotomaculum, Desulfobulbus, Desulfomicrobium, Desulfomonas, and Desulfovibrio genera belong to the intestinal microbiocenosis in humans and animals [1,22,23,24,46]. The knowledge on the interaction of SRB with other microorganisms in intestines is not sufficient.…”
mentioning
confidence: 99%